THE EFFECT OF USING CAKE ENGLISH APPLICATION TO IMPROVE STUDENTS SPEAKING SKILLS AT ISLAMIC SENIOR HIGH SCHOOL OF NURUL ISLAM SEKARBELA - Ihsanul Hidayat (Sinar Lima, 2024)
The speaking ability is not developed well as it is expected. Thus, the importance of speaking skill to EFL learners must be highly considered for teachers in finding an appropriate method to improve students speaking skill. The objective of this study was to discover the significant effect of Cake English Application on Students Speaking Skill. This research used a quantitative approach. The research design was a pre-experimental with one-group pre-test and post-test. The samples in this research were 27 students of second grade of Senior High School of Nurul Islam Sekarbela. The instrument used in this research was a test. The research findings showed that the mean score of the pre-test was 45.00, while the mean score of the post-test was 76,37 Furthermore, based on the T-test, the result of the mean score of the post-test was higher than the pre-test. It means that there was the difference between before and after the treatment was implemented. The sig. value of paired sample t-test was 0.000, the value is lower than 0.05 (0.000<0.05). It concluded that the statistical hypothesis: the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It means that Cake English application has significance effect to students speaking skills.